Answer:Second Step
Step-by-step explanation:
On the right side in step two you added -3b-15b, and ended up with -12b. This is incorrect. -3b-15b is actually -18b
Answer:
-3
Step-by-step explanation:
divide 7 on both sides -21/7 = -3
w=-3
Answer:
f(x) = 1/2(4 - x)(x - 1)(x - 2)
Step-by-step explanation:
Considering zero's and a coefficient, the function is:
f(x) = a(x - 4)(x - 1)(x - 2)
Considering y-intercept:
f(0) = a(0 - 4)(0 - 1)(0 - 2)
4 = a(-4)(-1)(-2)
4 = -8a
a = -1/2
So the function is:
f(x) = -1/2(x - 4)(x - 1)(x - 2) = 1/2(4 - x)(x - 1)(x - 2)
If i understand you are wanting to find the value of g
so if 2/5 of the unkown value g is equal to -14 you would find out that 1/5 g would be -7 so to find g you times -7 by 5 and get -35
g= -35